2019
DOI: 10.1029/2019jc015476
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Water Masses in the Shelf Region of the Bering and Chukchi Seas With Fluorescent Organic Matter

Abstract: Pacific water is an important nutrient source for sustaining biological production in the Chukchi Sea, western Arctic Ocean, which is one of the productive regions in the world. Therefore, to understand the impacts of future environmental changes on biological production in the sea, it is crucial to understand the origins, modification processes, and spatiotemporal variations of the water masses from the Bering Sea with changes in nutrient concentrations. To improve water mass analysis in the shelf regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
(122 reference statements)
1
11
0
Order By: Relevance
“…Biogeographically, the classification of tintinnid genera (Neritic, species largely restricted to nearshore waters; Boreal, species restricted to Arctic and Subarctic waters; Cosmopolitan, species distributed widely in the world ocean) was based on Pierce and Turner (1993) and Dolan and Pierce (2013) . The threshold for Pacific Inflow Water was 4 ° C as Yamashita et al (2019) in our results. Data of total surface heat flux (SHF = net solar radiation + net longwave radiation + sensible heat flux + latent heat flux) were obtained from the European Centre for Medium-Range Weather Forecasts (ECMWF).…”
Section: Methodssupporting
confidence: 69%
“…Biogeographically, the classification of tintinnid genera (Neritic, species largely restricted to nearshore waters; Boreal, species restricted to Arctic and Subarctic waters; Cosmopolitan, species distributed widely in the world ocean) was based on Pierce and Turner (1993) and Dolan and Pierce (2013) . The threshold for Pacific Inflow Water was 4 ° C as Yamashita et al (2019) in our results. Data of total surface heat flux (SHF = net solar radiation + net longwave radiation + sensible heat flux + latent heat flux) were obtained from the European Centre for Medium-Range Weather Forecasts (ECMWF).…”
Section: Methodssupporting
confidence: 69%
“…Optical properties including absorbing and fluorescing properties have been used to assess DOM composition and fate (Coble, 2007; Nelson & Gauglitz, 2016), and trace water masses in Arctic waters (Dainard and GuĂ©guen, 2013; Gonçalves‐Araujo et al., 2016; GuĂ©guen et al., 2014; Logvinova et al., 2015; Stedmon et al., 2011; Walker et al., 2009; Yamashita et al., 2019). Colored DOM (CDOM) is defined as the fraction of DOM (up to 25%; Benner, 2002) that has light absorbing properties in the ultraviolet (UV) and visible regions of the electromagnetic spectrum (Hansell & Carlson, 2002) whereas the fluorescent DOM (FDOM) refers to the DOM pool that fluoresces.…”
Section: Introductionmentioning
confidence: 99%
“…and Gonçalves-Araujo et al, 2016;GuĂ©guen et al, 2014;Logvinova et al, 2015;Stedmon et al, 2011;Walker et al, 2009;Yamashita et al, 2019). Colored DOM (CDOM) is defined as the fraction of DOM (up to 25%; Benner, 2002) that has light absorbing properties in the ultraviolet (UV) and visible regions of the electromagnetic spectrum (Hansell & Carlson, 2002) whereas the fluorescent DOM (FDOM) refers to the DOM pool that fluoresces.…”
mentioning
confidence: 99%
“…Until recently, various trends in the properties of these water masses have been reported in the Chukchi Sea (Ershova et al, 2015b;Corlett and Pickart, 2017;Danielson et al, 2017;Pickart et al, 2019). In particular, excellent analyses of water masses in this area have been performed by Pickart and colleagues (Pickart and Stossmeister, 2008;Pickart et al, 2010Pickart et al, , 2016Pickart et al, , 2019Brugler et al, 2014;Pickart, 2015, 2016;Pisareva et al, 2015;Corlett and Pickart, 2017;Linders et al, 2017;Lin et al, 2019); many previous studies have cited or applied Pickart's classifications when identifying water masses (e.g., Ershova et al, 2015a;Weingartner et al, 2017;Yamashita et al, 2019). Due to the purpose and region of this study, the water masses were identified with reference to the recent and well-organized methods of classification in Corlett and Pickart (2017) and Pickart et al (2019).…”
Section: Water Mass Identificationmentioning
confidence: 99%